2022
DOI: 10.1371/journal.pone.0271404
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school closure intervention during the third wave of the COVID-19 pandemic in Italy: Evidence from the Milan area

Abstract: Background In February 2021, the spread of a new variant of SARS-CoV-2 in the Lombardy Region, Italy caused concerns about school-aged children as a source of contagion, leading local authorities to adopt an extraordinary school closure measure. This generated a debate about the usefulness of such an intervention in light of the trade-off between its related benefits and costs (e.g. delays in educational attainment, impact on children and families’ psycho-physical well-being). This article analyses the epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Concerning the closure of educational institutions, most parishes did not have upper secondary schools or universities but did have primary and lower secondary schools affected by the lockdowns. Several previous studies have explored the specific effect of school closures during the COVID-19 pandemic using interrupted time series designs [8] , [9] , [10] and positive effects have been reported [8] , [9] , [10] , although Rotevatn et al . [8] in Oslo, Norway found that school closures were equally effective as targeted infection prevention and control measures in open schools in reducing student infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the closure of educational institutions, most parishes did not have upper secondary schools or universities but did have primary and lower secondary schools affected by the lockdowns. Several previous studies have explored the specific effect of school closures during the COVID-19 pandemic using interrupted time series designs [8] , [9] , [10] and positive effects have been reported [8] , [9] , [10] , although Rotevatn et al . [8] in Oslo, Norway found that school closures were equally effective as targeted infection prevention and control measures in open schools in reducing student infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…The school closure intervention produced a daily reduction in the risk of contagion by 4% in those aged 3-11 years and 12-19 years, and by 3% in those aged ≥20 years. The epidemic curve decreased first in school-aged children after the intervention and subsequently in the adult population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The closure of businesses, limited job openings, and increased competition for available positions have created a highly challenging environment for these young individuals (Carta & De Philippis, 2021;Cefalo & Scandurra, 2021). At the same time, the pandemic has disrupted educational systems, leading to school and university closures, remote learning challenges, and limited access to vocational training programs (Consolazio et al, 2022;Pastore & Choudhry, 2022;Pozzoli et al, 2022). This disruption has significantly impacted NEETs (Fiaschi & Tealdi, 2022), as they often lack the necessary qualifications and skills that employers demand .…”
Section: Introductionmentioning
confidence: 99%